Exploring geographical differences in the incidence of colorectal cancer in the Norwegian Women and Cancer Study: a population-based prospective study - Oyeyemi,Sunday Oluwafemi; Braaten,Tonje; Botteri,Edoardo; Berstad,Paula; Borch,Kristin Benjaminsen (Clinical Epidemiology, 2019)
Sunday Oluwafemi Oyeyemi,1 Tonje Braaten,1 Edoardo Botteri,2,3 Paula Berstad,2 Kristin Benjaminsen Borch11Department of Community Medicine, Uit-the Arctic University of Norway, Tromsø, Norway; 2Department of Bowel Cancer Screening, Cancer Registry of Norway, Oslo, Norway; 3Norwegian National Advisory Unit for Women’s Health, Women’s Clinic, Oslo University Hospital, Oslo, NorwayPurpose: Norway has experienced an unexplained, steep increase in colorectal cancer (CRC) incidence in the last half-century, with large differences across its counties. We aimed to determine whether geographical distribution of lifestyle-related CRC risk factors can explain these geographical differences in CRC incidence in Norwegian women.Methods: We followed a nationally representative cohort of 96,898 women with self-reported information on lifestyle-related CRC risk factors at baseline and at follow-up 6–8 years later in the Norwegian Women and Cancer Study. We categorized Norwegian counties into four county groups according to CRC incidence and used Cox proportional hazard models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for risk factors. We used the Karlson, Holm, and Breen (KHB) method of mediation analysis to investigate the extent to which the risk factors accounted for the observed differences in CRC incidence between counties.Results: During an average of 15.5 years of follow-up, 1875 CRC cases were diagnosed. Height (HR=1.12; 95% CI 1.08, 1.17 per 5 cm increase); being a former smoker who smoked ≥10 years (HR=1.34; 95% CI 1.15, 1.57); or being a current smoker who has smoked for ≥10 years (HR=1.28; 95% CI 1.12, 1.46) relative to never smokers was associated with increased CRC risk. Duration of education >12 years (HR=0.78; 95% CI 0.69, 0.87) vs ≤12 years, and intake of vegetables and fruits >300 g (HR=0.90; 95% CI 0.80, 0.99) vs ≤300 g per day were associated with reduced CRC risk. However, these risk factors did not account for the differences in CRC risk between geographical areas of low and ...